Risk of bacterial bloodstream infection does not vary by central-line type during neutropenic periods in pediatric acute myeloid leukemia. (25th February 2023) - Elgarten, Caitlin W.; Otto, William R.; Shenton, Luke; Stein, Madison T.; Horowitz, Joseph; Aftandilian, Catherine; Arnold, Staci D.; Bona, Kira O.; Caywood, Emi; Collier, Anderson B.; Gramatges, M. Monica; Henry, Meret; et al.
Abstract: Background: Bloodstream infections (BSIs) are a frequent cause of morbidity in patients with acute myeloid leukemia (AML), due in part to the presence of central venous access devices (CVADs) required to deliver therapy. Objective: To determine the differential risk of bacterial BSI during neutropenia by CVAD type in pediatric patients with AML. Methods: We performed a secondary analysis in a cohort of 560 pediatric patients (1, 828 chemotherapy courses) receiving frontline AML chemotherapy at 17 US centers. The exposure was CVAD type at course start: tunneled externalized catheter (TEC), peripherally inserted central catheter (PICC), or totally implanted catheter (TIC). The primary outcome was course-specific incident bacterial BSI; secondary outcomes included mucosal barrier injury (MBI)-BSI and non-MBI BSI. Poisson regression was used to compute adjusted rate ratios comparing BSI occurrence during neutropenia by line type, controlling for demographic, clinical, and hospital-level characteristics. Results: The rate of BSI did not differ by CVAD type: 11 BSIs per 1, 000 neutropenic days for TECs, 13.7 for PICCs, and 10.7 for TICs. After adjustment, there was no statistically significant association between CVAD type and BSI: PICC incident rate ratio [IRR] = 1.00 (95% confidence interval [CI], 0.75–1.32) and TIC IRR = 0.83 (95% CI, 0.49–1.41) compared to TEC. When MBI and non-MBI were examined separately, results were similar. Conclusions: In this large, multicenter cohort of pediatric AML patients, we found no difference in the rate of BSI during neutropenia by CVAD type. This may be due to a risk-profile for BSI that is unique to AML patients.